Solusi sampah plastik: Pemanfaatan sampah plastik bisa setara dengan emas - Aisyah, Dwi Danty (Maliki Interdisciplinary Journal, 2024)
Garbage is a problem that cant be avoided because it is closely related to basic needs and daily human activities. Waste itself is often interpreted as residual material in solid form after humans have done a job or activity and are no longer wanted and no longer provide benefits. Lately the problem of waste has increased, especially plastic waste which is difficult to decompose and takes hundreds of years to destroy plastic waste, besides that plastic contains the chemical Bisphenol A which causes the adverse effects of smoke when burned. Plastic waste not only pollutes the environment but also pollutes water, air and soil cause some people who are not aware of environmental cleanliness throw plastic waste into rivers and burn it. Several village residents in Jakarta themselves have actually made innovations by processing plastic waste to bring a use value and a high selling price realized by the former governor of DKI Jakarta Basuki Tjahaja Purnama (AHOK), establishing a green open space namely the Child Friendly Integrated Space or known as RPTRA in every village. A corner of Jakarta which recruits housewives to do creativity from plastic bottles. It is hoped that plastic waste can be managed to provide benefits and high value.